Dynamic wireless charging lanes location model in urban networks considering route choices. (June 2022) - Tran, Cong Quoc; Keyvan-Ekbatani, Mehdi; Ngoduy, Dong; Watling, David
Abstract: Wireless charging technologies have now made it possible to charge while driving, which offers the opportunity to stimulate the market penetration of electric vehicles. This paper aims to support the system planner in optimally deploying the wireless charging lanes on the network, considering traffic dynamics and congestion under multiple vehicle classes. The overall objective is to maximise network performance while providing insights into traffic propagation patterns over the network. A multi-class dynamic system optimal model is adopted to compute an approximate representation of the dynamic traffic flow. As a result, the problem is formulated as a mixed-integer linear program by integrating the dynamic routing behaviour into the charging location problem. Finally, the proposed framework has been tested on different sized test-bed networks to examine the solution quality and illustrate the model's efficacy. Highlights: A mixed-integer linear framework for wireless charging lane deployment is introduced. Maximise system performance while providing more insights into flow propagation. Consider traffic dynamics and congestion under multiple vehicle classes. A multi-class dynamic system optimal model with EVs is adopted.